PENGARUH DOSIS INOKULUM CENDAWAN MIKORIZA ARBUSKULA (GIGASPORA ROSEA) DAN PUPUK NITROGEN TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA - Ade Wachjar; Yadi Setiadi; Tirsa Rachma Hastuti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1998)
The experiment was aimed to study the effect of Gigaspora rosea inoculant and nitrogen fertilizer on the growth of coffee Robusta seedling. Coffee seedling which were used came from seedling of hybrid variety from BP 42 and BP 358 crossing, age 1 month. Micorrhiza fungi inoculations which were used came from Gigaspora rosea species. The experiment was conducted at Sukamantri Experiment Station Bogor Agriculture University, from December 1996 to August 1997. The experiment was arranged in Randomized Block Design with three replications. The first factor was dosage of micorhiza inoculation, consisted of 0, 5, 10 and 15 g/seedling. The  second factor was dosage of nitrogen consisted of 0, 1.5, 3.0 and 4.5 g/seedling. Fungi inoculation treatment in the dosage 15 g/seedling showed the highest infection percentage but can not increase the growth of coffee seedling. Fungi inoculant in the dosage 5 g/seedling gave the best growth level, showed by variety height of seedling, trunk diameter; leaves total and leaves area, shoot and root biomass, compare to the other fungi inoculation dosages. The highest level of nitrogen in leaf was found in the dosage 4.5 g/seedling. Fungi inoculation in the dosage 5 g/seedling and nitrogen fertilizer in the dosage 3 g/seedling gave the highest level of leaves area and shoot biomass, compare to the other treatment combinations.